Analisis dan Perancangan Aplikasi Wisata Di Daerah Bogor Berbasis Android - Nurdin, Sam Ali; Abdurrazaq, Iqbal; Aldiansyah, Muhammad Arie (Universitas Trilogi, 2018)
In the present era, it is easy to fin information, but not all information obtained is valid information. Many tourists want to know about a place to visit. In addition, due to lack of promotion by the government, so many tourist attractions that have the potential to increase icnomes many people doesn’t know about the location of tourism. Bogor is the largest area attract tourists, especially local tourists. But many tourist attractions in the area of Bogor that has not been sought by the tourists. Researchers assume that it takes an applications that provide accurate information to increase tourist in Bogor, to reduce the shortage and make it easier for tourists to know information about the sights to be visited, researchers try to find a solution.